Inovasi model time token arends berbantuan media flipaclip untuk pembelajaran menulis cerita fiksi sekolah dasar - Diva Retno Maharani; Septi Yulisetiani (Jurnal Pendidikan Dasar, 2025)
Writing skills are important for elementary school students to support learning success. Problems in writing stories in elementary school occur in the prewriting stage and the writing stage. Students have difficulty developing ideas, difficulty expressing ideas in sequence, and difficulty connecting between story structures. For this reason, it is necessary to innovate appropriate learning models to maximize the learning outcomes of writing stories in elementary schools. Some of the learning models that have been applied in learning to write fiction stories are the roundtable, word square, and reciprocal teaching models. This research aims to find an innovative learning model for learning to write fiction stories for elementary school students. This study aims to find a learning model to support the implementation of learning to write fiction stories. Data were obtained from literature studies from learning model research to write fictional stories, interviews with teachers, and observations in elementary schools. The data validation technique uses source triangulation techniques and triangulation techniques. The learning steps of Time Token Arends include group division, material discussion, coupon distribution, use of coupons for learning, and evaluation. The innovation carried out at the group division stage is group division by considering the diversity of student competencies. Innovation in material discussions with a diversity of stories and forms of stories presented with flipaclip media. The innovation in coupons is that they are presented with attractive designs. Each coupon has a story structure to discuss. The innovation of the model can create a positive response of students as seen from their enthusiasm during learning, activeness in the practice of writing stories and increasing students' grades.